HIV/AIDS - World Bank (Washington, DC, 2012)
The epidemic spread of HIV/AIDS has been ferocious, posing a great threat, not only to public health, but to social sectors, and to development itself, while the fiscal cost of HIV/AIDS is significant as well. A set of effective prevention interventions include: changing behavior through communication; making the use of condoms, diagnosis, and treatment of sexually transmitted diseases, including counseling and testing, available and affordable; ensuring a safe blood supply; and, preventing parent-to-child transmission. In addition, countries should consider implementing programs to provide cost-effective management of common opportunistic infections. Similarly, community-based, and home-based care should be made available, in addition to traditional hospital care, particularly in countries with a generalized epidemic. Lessons convey the vital need for early action, supported by community participation, targeting the most vulnerable, and prioritizing interventions, while governments should be committed to its prevention, control, and funding. Additionally, nongovernmental organizations' participation plays a decisive role against the epidemic spread, in their capacity for social mobilization, and in reaching marginal groups.